Early detection of health problems in early childhood - Arini, Merita; Primastuti, Harumi Iring (Community Empowerment, 2025)
Preschool-aged children are at risk of various health problems. This community empowerment initiative aims to conduct early detection of health issues in young children while simultaneously educating teachers on simple anthropometric measurements. The activities included mentoring in child anthropometric measurements, health examinations, and discussions of health examination results. The findings from the examination of 58 young children revealed that the most common health problems were dental caries and tonsillitis. Additionally, teachers demonstrated competence in conducting anthropometric measurements, but their capacity for data interpretation needs further improvement. Parental involvement, teacher capacity enhancement, and regular health check-ups are crucial factors in monitoring children's health.